2018
DOI: 10.3390/toxics6030044
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of NOS3 G894T Polymorphisms with Air Pollution on the Risk of Ischemic Heart Disease Worldwide

Abstract: The purpose of this updated meta-analysis was to investigate the effect of nitric oxide synthase-3 (NOS3) G894T polymorphisms, air pollution and their interaction on ischemic heart disease (IHD) risk across populations worldwide. Recursive partition trees, nonlinear association curve fit and geographic information system maps were incorporated to verify results of conventional pooled analyses for sources of heterogeneity. Results from 61 studies (16,219 cases, 12,222 controls) revealed a significant increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
(131 reference statements)
0
1
0
1
Order By: Relevance
“…NOS3 is a vasoprotective gene [31] that regulates vascular tone, blood pressure and platelet aggregation [32]. Research reports have shown that NOS3 can affect metabolism in the urea cycle of the methylation pathway, which is essential for preventing systemic inflammation [33]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NOS3 is a vasoprotective gene [31] that regulates vascular tone, blood pressure and platelet aggregation [32]. Research reports have shown that NOS3 can affect metabolism in the urea cycle of the methylation pathway, which is essential for preventing systemic inflammation [33]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ТТ-генотип полиморфизма гена NOS3 был связан с риском атеросклеро- [35]. TT и GT генотипы были ассоциированы с риском ИБС [36,37] и АГ [38]. Результаты нашего исследования согласуются с исследованием Campedelli с соавт., где наличие GG-генотипа повышало предрасположенность к атеросклерозу [39].…”
Section: результаты и обсуждениеunclassified